PENERAPAN GRID COMPUTING UNTUK MENGKOMPILASI PROGRAM BERBAHASA C/C++ - Indrianingsih, Yuliani; Wintolo, Hero; Sari, Ika Kartika (SENATIK STT Adisutjipto, 2013)
Grid computing is a group of computers that connected to computer network and working together to complete a certain task. The computers inside must be coheren so the processors can work evenly when given a task from server. Grid computing can be used in many areas and purpopes, and in this research it will be used to compile C/C++ program. Compilation is a process to transform a human readable source code into a computer readable code. The compilation process will take place in a personal computer (PC). By using grid system in compilation process, the waiting time of a source code will be reduced as the compilation task will be divided among the computers. For that reason a C/C++ compiler software that using grid computing will be made. The task will be distributed among the computers inside the grid. It can also help someone who want to compile C/C++ source code but he doesn’t have the compiler on his PC.